Sub-bandage pressure changes in canine hindlimbs after re-application of custom rigid fiberglass splints - Brandon Thibodaux; Kendra Eginton; Wanda Gordon-Evans (BMC Veterinary Research)
Abstract Background While limited information is available, it is possible that high or low sub-bandage pressures cause injury with external coaptation. Fiberglass casting tape is a common splinting material that is custom made for the first bandage and reused in subsequent bandage changes. The aim of this preliminary study was to determine sub-bandage pressure changes in canine hindlimbs between initial splint placement and replacement of the bandage by a different person. The hypothesis was that there would be a clinically meaningful change in sub-bandage pressures with reapplication of the splint in at least one location. Sub-bandage pressures were measured at five different anatomic locations on each of 11 canine hind limbs with dogs standing and in lateral recumbency after customizing a fiberglass lateral tarsal splint for each dog. A second clinician then reapplied the bandage, reusing the same fiberglass splint. Second bandages failed if there was a change in pressure of 20 mmHg at any location. Results Ten of 11 bandages failed (90%). All but one location failed due to increases in pressure. There were significant changes between lateral recumbency and standing pressures, but there was no consistent pattern of these changes among the dogs. Conclusion There are changes in sub-bandage pressures when the splint is reused in 90% of bandages. In addition, changes in pressure occur unpredictably when transitioning from lateral recumbency to standing. Further study of the relationship of sub-bandage pressures to bandage complications is vital to help establish safe ranges and inform bandaging improvements.